Integration of Moth-Flame Optimization with Lattice-Based Cryptography for Post-Quantum IoT Data Protection - Ranjan Kumar Gupta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The rapid proliferation of Internet of Things (IoT) ecosystems has resulted in unprecedented volumes of sensitive information being transmitted across interconnected devices and cloud platforms, raising significant concerns regarding data protection and confidentiality. Conventional cryptographic frameworks are increasingly vulnerable to emerging threats, particularly with advancements in quantum computing capabilities. This research introduces a novel encryption methodology that synergistically combines Moth-Flame Optimization (MFO) with Lattice-Based Cryptography (LBC). LBC offers robust post-quantum security as an alternative to traditional cryptographic approaches, while MFO enhances the key generation process through sophisticated optimization techniques. This dual-layer framework strengthens cryptographic key generation while ensuring comprehensive security for IoT data transmissions to cloud infrastructure. The integrated MFO-LBC approach delivers a secure, scalable, and computationally efficient solution that addresses limitations inherent in conventional encryption schemes, providing resilience against both classical and quantum-based attacks.